Contribuições da educação problematizadora ao ensino de química em uma escola pública do estado de São Paulo - Alioto, Marcelo Rodrigo (2015)
Science education in Brazilian Basic Education has presented successively, unsatisfactory performance in external assessments of performance. There is an urgent need for change in this scenario in which does not teach what you must and that discourages the student learning. This work attempts to find ways to insert in the curriculum of Chemistry in the State of São Paulo, problematizing education conceived by Paulo Freire and manipulated by pedagogical moments of Demétrio Delizoicov. To do this, we applied the research in a public school in the city of Sertãozinho-SP, with the theme of cultivation of sugar cane, theme that is part of the daily life of the city, since it is the crop that moves the economy of the region. Search results allow us to conclude that it is possible to work this issue with the practice of Freire, but not without encountering difficulties in their implementation. Keywords: Problematizing Education; Teaching moments; Chemistry Teaching.